Stevens' handbook of experimental psychology - Pashler, Harold E.; Stevens, Stanley Smith (New York : John WIley and Sons, 2002)
Sadržaj: v. 1 -- Sensation and perception : Steven Yantis, volume editor -- v. 2 -- Memory and cognitive processes : Doulgas Medin, volume editor -- v. 3 -- Learning, motivation, and emotion : Randy Gallistel, volume editor -- v. 4 -- Methodology in experimental psychology : John Wixted, volume editor
Vol.1: Sensation and perception
Vol.2: Memory and cognitive processes
Vol.3: Learning, motivation, and emotion
Vol.4: Methodology in experimental psychology
Keywords: eksperimentalna psihologija